The Accuracy of Using the Moving Average Cross Indicator in Technical Analysis of Indonesian Banking Stocks - Endang Sri Apriani; Kety Lulu Agustin; Dessy Handa Sari; Nurul Musfirah Khairiyah (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2026)
One popular technique for financial decision-making is the moving average cross. This indicator provides signals about future stock price movements. However, the accuracy of this indicator's signals will be evaluated specifically on banking stocks listed on the Indonesia Stock Exchange. Thirty Indonesian banking companies listed on the main trading board in 2026 were selected as the research stocks. A purposive sampling procedure was used to select the research subjects, with issuers on the main board having assets exceeding 100 billion Rupiah and having been listed on the market for at least three years. Issuers on the main board are considered large issuers and can attract investors' attention. The signals provided by the 30 research subjects will then be tested using logistic regression techniques using SPSS. This approach works well for research using moving averages that have been converted into dummy data. Statistical test results indicate that the moving average cross movement is insufficient to decide which banking stocks to purchase; only 46.67% of the signals from the moving average move in accordance with the signal. More comprehensive indicators in technical analysis can be added to the analysis to make decisions and pay attention to the fundamental level of the emiten.